2021
DOI: 10.1042/cs20201290
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate and fibroblast growth factor 23 in diabetes

Abstract: Diabetes is associated with a strongly elevated risk of cardiovascular disease, which is even more pronounced in patients with diabetic nephropathy. Currently available guideline-based efforts to correct traditional risk factors are only partly able to attenuate this risk, underlining the urge to identify novel treatment targets. Emerging data point towards a role for disturbances in phosphate metabolism in diabetes. In this review, we discuss the role of phosphate and the phosphate-regulating hormone fibrobla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 182 publications
0
14
0
Order By: Relevance
“…A lower level of 25(OH)D might be caused by ineffective synthesis in skin upon exposure to ultraviolet B radiation and reduced nutritional intake ( 33 ). The deregulation of Fibroblast growth factor 23 (FGF23), an essential regulator to maintain phosphate and calcium homeostasis ( 34 ), could be another important reason to suppress the conversion of inactive 25(OH)D into active 1,25(OH) 2 D in diabetic patients ( 35 ). In our study, we also demonstrated that low level of 25(OH)D is an important risk factor for massive proteinuria and renal function decline.…”
Section: Discussionmentioning
confidence: 99%
“…A lower level of 25(OH)D might be caused by ineffective synthesis in skin upon exposure to ultraviolet B radiation and reduced nutritional intake ( 33 ). The deregulation of Fibroblast growth factor 23 (FGF23), an essential regulator to maintain phosphate and calcium homeostasis ( 34 ), could be another important reason to suppress the conversion of inactive 25(OH)D into active 1,25(OH) 2 D in diabetic patients ( 35 ). In our study, we also demonstrated that low level of 25(OH)D is an important risk factor for massive proteinuria and renal function decline.…”
Section: Discussionmentioning
confidence: 99%
“… 32 Hyperphosphatemia has also been noted in diabetes, especially in the context of diabetic nephropathy. 33 Therefore, poor renal function may have a mediating effect between phosphate retention and insulin resistance. However, although this study found a significant association between higher serum phosphate and existing kidney disease in women (p<0.001), serum phosphate was not associated with kidney disease development (p=0.411), nor was baseline kidney disease a significant contributor to diabetes (p=0.526).…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of hyperphosphatemia in CKD patients is heightened with the decline in renal function. 3,4 A rise in serum phosphate level occurs upon CKD progression, showing that the phosphate homeostasis compensation mechanism may remain effective up until stage 3a of CKD. 13 In advanced-level CKD (stage 3b), the kidney will no longer be able to compensate for phosphate burden adequately when the eGFR falls below 45 mL/min/1.73 m 2 , leading to hyperphosphatemia.…”
Section: Discussionmentioning
confidence: 99%
“…FGF-23 reduces calcitriol production, which also reduces phosphate and calcium absorption in the intestine, causing hypocalcemia. 3,4 In stage 3b CKD, the concentration of phosphate begins to rise, showing that the compensation mechanism is no longer adequate to preserve the phosphate balance and to prevent hyperphosphatemia. 4,5 The application of calcium-phosphate binders and calcitriol in CKD normalizes phosphate and calcium levels in the blood.…”
Section: Introductionmentioning
confidence: 99%